Efficiency enhancement of solar PV powered micro-integrated high frequency isolated vehicle battery charging converter - Jawahar Marimuthu; Jayasankar V; Karthik Kumar K; Edward Rajan S (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This Paper proposes a method to improve the efficiency of charging the battery used in autonomous electric vehicle powered by foldable roof-mounted solar photovoltaic (PV) generation system. The conventional vehicle battery charging application from solar PV consists of a boost converter in the frontend followed by a full bridge converter with discrete switches. Here an attempt is made on the total scheme with a micro integrated package to have better conversion efficiency with high power density. The total system is controlled digitally incorporating zero voltage transition (ZVT) in the full bridge conversion. A typical specification with a power level of 300-400 W was targeted and achieved.